2017
DOI: 10.1371/journal.pone.0175897
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes from a cohort of patients with acute kidney injury subjected to continuous venovenous hemodiafiltration: The role of negative fluid balance

Abstract: BackgroundSeveral factors influence the outcomes in acute kidney injury (AKI), especially in intensive care unit (ICU) patients. In this scenario, continuous renal replacement therapies (CRRT) are used to control metabolic derangements and blood volume. Knowing this fact, it may be possible to change the course of the disease and decrease the high mortality rate observed. Thus, we aimed to evaluate the main risk factors for death in AKI patients needing CRRT.ResultsThis was a prospective, observational cohort … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 47 publications
0
7
0
Order By: Relevance
“…This action is currently evaluated in a prospective trial (NCT03275792). In critically ill adult patients in general [ 212 , 213 ], and in those under renal replacement therapy specifically [ 214 , 215 ], fluid balance has been shown to influence survival. Altogether, these results call for increased alertness regarding fluid resuscitation in critically ill adults with STEC-HUS.…”
Section: Managementmentioning
confidence: 99%
“…This action is currently evaluated in a prospective trial (NCT03275792). In critically ill adult patients in general [ 212 , 213 ], and in those under renal replacement therapy specifically [ 214 , 215 ], fluid balance has been shown to influence survival. Altogether, these results call for increased alertness regarding fluid resuscitation in critically ill adults with STEC-HUS.…”
Section: Managementmentioning
confidence: 99%
“…However, there is no consensus on the optimal fluid management for such patients [812]. Several recent studies revealed that an increase of cumulative fluid balance (CFB) was significantly associated with an increase in mortality risk in critically ill patients [13–17], while Balakumar et al showed that both positive and negative fluid balance were associated with higher mortality rates compared with even fluid balance [18]. Furthermore, Silversides et al reported that active removal of fluid using RRT in critically ill patients was associated with less survival benefit compared with standard care [1921].…”
Section: Introductionmentioning
confidence: 99%
“…In our study, mortality was significantly higher in patients with lactic acidosis (p<0.001, chi-square test). In a study evaluating patients who underwent CVVHDF, Santos et al emphasized that reduced urine output was an independent predictor of mortality [13]. Other studies with similar results also showed this effect was not associated with creatinine level [14].…”
mentioning
confidence: 94%